2015
DOI: 10.1186/s12889-015-2684-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between social and built environments and leisure-time physical activity among Chinese older adults - a multilevel analysis

Abstract: BackgroundSocial and physical environments are not only hypothesized to influence physical activity (PA), they are also interrelated and influence each other. However, few studies have examined the relationships of PA with social and physical environments simultaneously. Accordingly, the current study aims to examine the association between physical and social attributes of neighborhood with leisure-time physical activity (LTPA) among the Chinese elders.MethodsBy employing a two-stage stratified random samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 68 publications
(70 reference statements)
1
70
1
Order By: Relevance
“…The scales used to measure these dimensions were developed by Mujahid and colleagues (33). As described in detail previously (31), the original scale was initially translated into Chinese, and the Chinese version was then translated back into English to verify that the content of the original scale was maintained. The aesthetic quality (AQ) subscale consisted of 5 items, the walkability subscale consisted of 7 items, the social interaction with neighbors subscale consisted of 5 items, and the social cohesion subscale consisted of 4 items.…”
Section: Attributes Of Neighborhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…The scales used to measure these dimensions were developed by Mujahid and colleagues (33). As described in detail previously (31), the original scale was initially translated into Chinese, and the Chinese version was then translated back into English to verify that the content of the original scale was maintained. The aesthetic quality (AQ) subscale consisted of 5 items, the walkability subscale consisted of 7 items, the social interaction with neighbors subscale consisted of 5 items, and the social cohesion subscale consisted of 4 items.…”
Section: Attributes Of Neighborhoodmentioning
confidence: 99%
“…The subdistrict has a stable population structure and built environment, which make it a suitable place to examine the effects of the perceived social and physical attributes of a neighborhood on health. The study design and sampling approach has been described previously (31). Briefly, the first stage consisted of the selection of 47 neighborhoods by purposive sampling that took into account environmental factors such as accessibility to services, aesthetics, and street connectivity.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Meanwhile, the higher percentage of local commerce reflects greater access to common destinations such as restaurants, supermarkets, shops, and services, which promotes commuting on foot and other active behaviors 13,18 . The absence or low proportion of paved streets in neighborhoods can also contribute to a lower supply of services focused on the prevention of obesity, such as workout gyms and recreational clubs 39 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Greater walkability could advance the volume, opportunity, and motivation of physical activity and less sedentary behavior. 12,13 It is necessary to use urban design to build healthy and walkable neighborhoods. 14 Previous studies have demonstrated several features of walkability in a neighborhood environment.…”
Section: Prevention Of Non-communicable Diseasesmentioning
confidence: 99%
“…Population/residential density, street connectivity, traffic, aesthetic, mixed land uses (e.g., the accessibility of public infrastructure, such as parks, sport facilities, shops), socioeconomic status (SES), and the crime rate are all indicators of walkability. 6,11,12,15 The measurement of indicators of walkability can be subjective (e.g., perceived questionnaires) or objective (e.g., open data and geographic information systems).…”
Section: Prevention Of Non-communicable Diseasesmentioning
confidence: 99%